PENERAPAN KEBIJAKAN PADA PERAWAT DAN PETUGAS MEDIS DALAM PENGELOLAAN LIMBAH MEDIS DAN NON MEDIS TERHADAP HYGIENE DAN SAITASI DI WILAYAH KERJA PUSKESMAS BATUGANA - Ramadonna, Yusnita (Jurnal Inovasi Kesehatan Masyarakat, 2021)
The World Health Organization (WHO) reports that 15% of waste generated by health services is infectious waste, 1% chemical waste, 3% pharmaceutical waste, 1% radioactive waste. The purpose of this study was to determine the relationship between knowledge, attitudes, training, and specifications of health workers on medical and non-medical waste management in public health centers. This research was conducted using a cross-sectional method. The sample was 96 health workers at Batu Gana Health Center. The sampling technique was carried out by consecutive sampling. Data were analyzed using chi-square test for bivariate test and logistic regression for multivariate test at significant level Î± = 0.05). The results showed that there was a relationship of knowledge (p <0.05), RP 3.60; 95% CI (1.28-10.09), health personnel specifications (p <0.05), RP 7.54; 95% CI (4.79-19.72) with medical and non-medical waste management while attitude (p> 0.05), length of work (p> 0.05), and training in the last 1 year (p> 0, 05) no significant relationship was found. It can be concluded that there is a relationship between knowledge and specifications of health workers with medical and non-medical waste management with the most dominant relationship between health personnel specifications. It is recommended that the head of the Batu Gana Puskesmas be able to provide training to medical personnel at least once a year to improve medical and non-medical waste management.